Designation of harmonic estimation ANN model using experimental data obtained from different produced induction motors - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
Artificial Neural Network (ANN) technique has been used for the prediction of voltage THD (Total Harmonic Distortion), mainly from input and output measurements of three phase, squirrel cage induction motors fed from a pulse width modulation inverter voltage supply. The induction motors have different construction, different power and produced by different firm. A sinusoidal pulse-width modulation (SPWM) inverter feeding three-phase induction motors were tested up to first thirty harmonic voltage components at different loads. The results show that the artificial neural network model produces reliable estimates of voltage THD.
Keywords: Artificial Neural Network; Total Harmonic Distortion; harmonic estimation; induction motors